Analisis Kepuasan Pasien terhadap Pelayanan Kesehatan Ibu dan Anak (KIA) pada Masa Pandemi Covid-19 : Analyzing patient satisfaction with maternal and child health services during the Covid-19 Pandemic - Metha Fahriani; Dewi Aprilia Ningsih I. (Jurnal Bidan Cerdas, 2021)
Introduction:In early 2020, the world was shocked by the outbreak of the coronavirus disease 2019 (COVID-19). The spread of this disease has had a wide impact, one of which is services namely Puskesmas (Primary Health Care), including Maternal Health and Child. Purpose: to analyzing patient satisfaction with maternal and child health services during the Covid-19 Pandemic. Methods: This research uses descriftive analysis with cross sectional design. Sampling in this study using accidental sampling with a sample size of 30 people, collecting data using questionnaires that have been tested for validity and reliability. Data analysis used univariate, bivariate pearson chi-square, and multivariate logistic regression. Results: Pearson Chi-Square test obtained ρ-value < α (0,05) on variables dimensions of reliability ρ: 0,019, dimensions of responsiveness ρ: 0,019, dimensions of assurance ρ: 0,009, dimensions of empathy ρ: 0,000, and tanggibles variables ρ: 0,013. Conclusion: The variable that has the greatest relationship with patient satisfaction with maternal and child health services during the Covid-19 Pandemic is the Empathy Dimension, with largest regression coefficient (β). It is hoped that health services will focus on service indicators even in the Covid-19 pandemic